Strategies for Memorising the Qur'an Using the Tikrar Method at the Majelis Tafsir Al-Qur'an Tahfiz Centre for Girls in Karangpandan, Karanganyar - Talitha Javier; Dartim Dartim (Universitas Islam Negeri Sumatera Utara, 2026)
This study aims to describe the strategy of memorizing the Qur'an using the tikrar method in fostering the memorization of female students at the Tahfidz Center Putri Karangpandan Al-Qur'an Interpretation Council (MTA) Islamic Boarding School. The tikrar method is an intensive repetition technique that has been proven effective in producing memorization that is Mutqin (strong and inherent) and valid (correct according to the rules of tajwid). This study employs a qualitative-descriptive methodology, collecting data through literature reviews, interviews, and observations. An interactive analysis model is used for analysis. The study's findings show that the merging of spiritual and technical elements supports the tahfidz strategy's effectiveness at this Islamic boarding school. The spiritual aspect in the form of tazkiyatun nafs (purification of the heart) is implemented through the habituation of manners, strengthening intentions, and fostering morals before the memorization process begins. In the technical aspect, the tikrar method is implemented through the following stages: (1) Ziyadah, namely the addition of new memorization with layered repetition; (2) Juziyah, namely the submission of one juz in its entirety as an evaluation of the quality of memorization; (3) Tasmi' Marhalah, namely the payment of a number of juz as a condition for increasing the level; and (4) Semester Tahfidz Exam, which is a comprehensive evaluation of memorization during one learning period.